Rumen ecology research planning. Proceedings of a workshop - Wallace, R.J.; Lahlou-Kassi, A. (International Livestock Research Institute, 1995)
This workshop was conducted to identify and prioritise areas of rumen ecology which are promising for their potential impact on improving nutrition status of tropical ruminants, to develop a rumen ecology research programme for ILRI based on relevance to developing countries and ILRI's comparative advantage vis-a-vis other institutions, to identify potential collaborators in advanced research institutes, and to define model(s) of collaboration. Major topics of discussion include - potential application of rumen ecology manipulation to animal nutrition in developing countries, state of art in manipulation of the rumen microbial ecosystem, and state of art in bioengineering of rumen microorganisms.